Pré-Diagnóstico da Doença Fúngica Antracnose no Cultivo do Capsicum Annuum Através da Lógica Fuzzy - de Sousa, Roney; de Brito, Rhyan; de Sousa Ximenes, Janaide (Proceedings of the Regional School on Computing of Ceará, Maranhão, and Piauí (ERCEMAPI), 2020)
The use of Computational Intelligence techniques has been highlighted in solving the most diverse types of problems. Based on this perspective, a study was carried out through the implementation of a Fuzzy system aiming to use it as a diagnostic tool for anthracnose disease in a pepper garden. The methodology was based on the collection of samples of plants with characteristics of anthracnose disease used as input variables in Fuzzy. Three diagnostic tests were carried out with collected data, showing to be quite promising compared to the expected. The study showed the importance of using Fuzzy logic to aid in the detection of diseases such as anthracnose that attacks vegetables such as peppers.